Understanding zakat payments in Indonesia: A psychological perspective on muzakki behaviour - Soemitra, Andri; Marliyah; Julita, Julita (Universitas Negeri Surabaya, 2024)
The muzakki decision to pay zakat is influenced by behavioural finance, which considers psychological factors like emotions and beliefs. This research aims to establish a model for zakat payments that incorporates perceptions, financial behaviours, and religiosity among muzakki. This research analyses and evaluates what a practical and relevant model to be used by muzakki in behavioural finance-based zakat payment decisions in zakat management organisation, having good perceptions, financial behaviour, psychology, emotions, and religiosity, as well as a commitment to zakat payments in zakat management organisation is. His research indicates that money's psychology (X1) influences Muzakki's decision to pay zakat in behavioural finance. Perception (X2) and external locus of control (X3) do not affect this decision. The emotional quotient (Z) significantly impacts Muzakki's zakat decisions and moderates the psychology of money (X1) on these decisions. However, it does not moderate Perception (X2) about zakat payments. Lastly, the emotional quotient (Z) moderates the external locus of control (X3), affecting Muzakki's decision to pay zakat at management organisations in behavioural finance. Zakat management organisations can effectively tailor their strategies to align with behavioural finance principles, addressing the psychological and emotional factors driving Muzakki's decisions.